Lack of educational impact of video game addiction in children and adolescents diagnosed with ADHD: A cross-sectional study - Blasco-Fontecilla, Hilario; Menéndez-García, Ángela; Sanchez-Sanchez, Fernando; Bella-Fernández, Marcos (Frontiers in Psychiatry, 2023)
Introduction The use of video games has become widespread worldwide. Excessive use of video games is increasingly becoming a matter of concern, particularly in patients diagnosed with Attention Deficit Hyperactivity Disorder (ADHD). Currently, internet gaming disorder (IGD) is not included within the DSM-5-chapter Disorders related to substances and addictive disorders. Methods This is a post-hoc descriptive naturalistic study comparing children and adolescents diagnosed with ADHD with and without IGD. We used the 85% cut-off point of the test ADITEC-V for video game addiction to split our sample of ADHD patients into those with IGD (>=85%) and those without IGD (<85%). Results 13 (25%) out of the 51 children and adolescents with ADHD included in our study had an IGD. Patients with IGD had a first contact with internet, smartphones, and videogames at a very early age (5.67 ± 3.31, 6.33 ± 4.60, and 7.50 ± 2.61, respectively). However, only age at first contact with the internet was statistically significantly different when comparing ADHD patients with and without IGD (8.68 ± 2.71 vs. 5.67 ± 3.31, t = 3.166, df = 47, p = 0.01). Different neurodevelopmental, clinical, and neuropsychological measures converging in impulsivity is a risk factor for IGD. Unexpectedly, we found no association between IGD and poor academic achievement. Discussion Future studies may include randomized controlled trials for treating IGD, the study of social adjustment as a protective factor against developing an IGD, and the role of serious and non-serious video games in the development of an IGD, among others. Additional research is clearly needed on IGD.